(untitled) (Research, Society and Development, 2021)
The present study aimed to reflect on the repercussions of precarious work in health and the mental suffering faced by health professionals in the context of the pandemic of COVID-19 in Brazil. Content synthesis: this is a critical theoretical essay, based on the problematization of Provisional Measure 927 of 2020, applied to the context of the COVID-19 pandemic, as a way to legitimize the overexploitation of the health worker. Thus, it is understood that the dismantling of labor laws is something historical in Brazil. However, in the last three years, this aspect has intensified, finding in the context of the pandemic by the new coronavirus space to establish itself as a legitimate means. It is from this new onslaught by the Federal Government that the flexibilization of labor contracts, the increase in working hours, the reduction of rest time and release on occupational safety and health are established as a legal means. This worsens the precarious work and mental suffering of health professionals, due to the lack of recognition and work overload. Conclusion: it is essential to expand this debate in view of the negligence of the Brazilian Government, making it necessary new ways of reinventing class entities and labor bodies in order to protect social rights and preserve workers’ mental health.